Polyhydroxyalkanoates from palm oil : biodegradable plastics - Sudesh, Kumar , 1967- (SpringerBriefs in Microbiology, 2013)
The environmental problems caused by petroleum-based plastic and plastic waste have led to an increasing demand for biobased and biodegradable plastics, such as polyhydroxyalkanoates (PHAs). These polyesters are synthesized from carbon sources, e.g. sugar and plant oils, by various bacteria. This book highlights the potential of plant oils, especially palm oil, as a feedstock for PHA production. In addition, new PHA applications are discussed and the sustainability of PHA production from plant oils is critically examined.